O ensino da controladoria nos cursos de ciências contábeis das universidades federais brasileiras - Teixeira, Jéssica Frota Santos (2015)
The Controllership is a new field that is still in continuous progress. The understandings about this field are so deep. In today's scenario, considering that the knowledge about controllership has a fundamental importance for the development and training of the professional accountant it is considerable to know what is being offered by undergraduate programs realizing its features. This research has as main purpose to analyze the characteristics of the curriculum used in the teaching of controlling among the accounting programs within Brazilian Federal Universities. This study methodology is classified as exploratory and descriptive with using bibliographical and documentary techniques as well as the application of content analysis of documents that were made available on the websites of 34 federal universities used as a sample survey. Given the results it was found that within the content category, the subcategory context was the most discussed, mainly in relation to controllership function. Regarding to the bibliography category it was observed that the most cited author in the programs syllabus is Armando Catelli and in the category goals there was a divergence among the studied syllabus.